Factors Affecting the Implementation of Good Government Governance (GGG) and Its Implications for Performance Accountability - Marsuni, Nur Sandi; Rasulong, Ismail; Adzim, Faidul (Jurnal Ekonomi Balance, 2022)
This study aims to examine several critical issues, such as the influence of local government competence and professionalism of government internal control apparatus on the implementation of Good Government Governance (GGG), as well as the impact of Good Government Governance (GGG) on local government performance. The research method used is Literature Review Analysis. This study uses fifteen references, two Scopus articles, ten national articles, and three books on local government organizations in Indonesia. Our findings show that the implementation of GGG is influenced by the competence and professionalism of local government officials as well as government internal supervision, and the implementation of Good Government Governance (GGG) affects the accountability performance of local governments.